Sulfonated Graphene Aerogels Enable Safe‐to‐Use Flexible Perovskite Solar Modules. Issue 5 (22nd December 2021) - Li, Zhen; Wu, Xin; Li, Bo; Zhang, Shoufeng; Gao, Danpeng; Liu, Yizhe; Li, Xintong; Zhang, Ningbin; Hu, Xiaotian; Zhi, Chunyi; Jen, Alex K.‐Y.; Zhu, Zonglong
Abstract: The potential leakage of lead from degraded perovskite photovoltaics poses a threat to the ecosystem and human health, which is a severe hurdle for their commercialization, especially for flexible modules that are often integrated in applications used in daily living. To trap the lead from degraded flexible perovskite solar modules (PVSMs), sulfonated graphene aerogels mixed with polydimethylsiloxane are employed to serve as lead‐absorbing encapsulants on both sides of flexible PVSMs. The large specific area of sulfonated graphene aerogels and their high binding energy with Pb 2+ give them superior lead adsorption capacity in aqueous solution. Over 99% of Pb 2+ from the degraded flexible PVSMs can be captured by the encapsulant under different simulated conditions (scratching, bending, and thermal circling) to reduce the lead leakage to ≈10 ppb. Moreover, the lead from degraded flexible PVSMs can be minimized to far below the hazardous waste limit according to the resource conservation and recovery act regulation (RCRA). This work provides an effective strategy to realize safe‐to‐use perovskite‐based flexible electronics to facilitate their commercialization. Abstract : The potential leakage of lead from the degraded perovskite photovoltaic poses threats to the ecosystem. To trap the lead from degraded flexible perovskite solar modules (PVSMs), sulfonated graphene aerogels/polydimethylsiloxane is employed to serve as a lead‐absorbing encapsulant. Over 99% of Pb 2+ from the degraded PVSMs can be captured, which provides an effective strategy to realize safe‐to‐use perovskite‐based flexible electronics.